Current Trends in Volume Replacement Therapy and the Use of Synthetic Colloids in Small Animals—An Internet-Based Survey (2016) - Yozova, Ivayla D.; Howard, Judith; Sigrist, Nadja E.; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2017)
The use of synthetic colloids (SCs), particularly hydroxyethyl starch (HES), in people has changed in recent years following new evidence raising concerns about their efficacy and safety. Although fluid therapy guidelines for small animals are often extrapolated from human medicine, little information exists on current practice in veterinary medicine. The objective of the present study was to investigate current fluid selection, use of plasma volume expanders including SCs, and recent changes in their use in small animal practice. An internet-based survey was conducted, inviting veterinarians to report their practices in fluid resuscitation and colloid osmotic pressure support, their choice of SC, and perceived adverse effects and contraindications associated with SC use. There were 1134 respondents from 42 countries, including 46% general practitioners and 38% diplomates. Isotonic crystalloids, HES and hypertonic saline were chosen by most respondents for fluid resuscitation, and HES by 75% of respondents for colloid osmotic support. Dextran and gelatin were used by some European respondents. Human serum albumin was used more than canine albumin but 45% of respondents, particularly those from Australia and New Zealand, used no albumin product. The majority (70%) of respondents changed their practice regarding SCs in recent years (mostly by limiting their use), largely due to safety concerns. However, only 27% of respondents worked in an institution that had a general policy on SC use. Impaired renal function, coagulopathy and hypertension were most often considered contraindications; impaired coagulation tests and increased respiratory rate were the most frequently perceived adverse effects. The use of HES remains widespread practice in small animals, regardless of geographic location. Nevertheless, awareness of safety issues and restrictions on the use of SCs imposed in human medicine seems to have prompted a decrease in use of SCs by veterinarians. Given the paucity of evidence regarding efficacy and safety, and differences in cohorts between human and veterinary critical care patients, studies are needed to establish evidence-based guidelines specific for dogs and cats.